DINAMIKA KEPENDUDUKAN, PERTUMBUHAN EKONOMI, DAN KETAHANAN PANGAN: SEBUAH ANALISIS KUANTITATIF DI KOTA SUNGAI PENUH - Rahayu, Silvia; Harahap, Erni Febrina; Yadewani, Dorris (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to determine the effect of population and economic growth on food security in Sungai Penuh City. This is a quantitative study. The data used in this study are secondary data sourced from the Sungai Penuh City Statistics Agency (BPS), the Sungai Penuh City Food Security Office, the Population and Civil Registration Office, and publications from the Jambi Province Statistics Agency (BPS), and the Republic of Indonesia Statistics Agency (BPS RI). The analytical tools used were multiple linear regression, hypothesis testing, and the coefficient of determination. Based on the results, the model examining the effect of population and economic growth on food security in Sungai Penuh City was not statistically significant (Sig. F Change = 0.498 > ? 0.05). Although the multiple correlation coefficient (R = 0.543) indicates a moderate linear relationship, the R Square value of only 0.295 indicates that the two independent variables are only able to explain 29.5% of the variation in the dependent variable of food security in Sungai Penuh City